2013
DOI: 10.1002/jcph.181
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lamivudine combined with adefovir dipivoxil versus entecavir monotherapy in patients with hepatitis B-associated decompensated cirrhosis: A meta-analysis

Abstract: Whether the combination of lamivudine (LAM) plus adefovir (ADV) de novo is more effective than entecavir (ETV) monotherapy in patients with HBV-associated decompensated cirrhosis is still controversial. We searched seven randomized controlled trials that included 411 patients in this meta-analysis. There are 205 and 206 patients in these two groups separately. The pooled risk ratio (RR) and mean difference (MD) were used to assess the treatment effects. ETV monotherapy significantly improved Child-Turcotte-Pug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…The nucleotide analog adefovir dipivoxil has a clear-cut effect in treating acute and chronic hepatitis B hepatocirrhosis and has shown many advantages, such as clinical strengths of low drug resistance and light side effects ( 1 , 2 ). Apart from interfering with the DNA transcription directly, adefovir dipivoxil can adjust the immune function of the body, including cellular and humoral immunity ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide analog adefovir dipivoxil has a clear-cut effect in treating acute and chronic hepatitis B hepatocirrhosis and has shown many advantages, such as clinical strengths of low drug resistance and light side effects ( 1 , 2 ). Apart from interfering with the DNA transcription directly, adefovir dipivoxil can adjust the immune function of the body, including cellular and humoral immunity ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were also some studies exploring the efficacy of LAM combined with ADV versus ETV monotherapy in patients with hepatitis B associated decompensated cirrhosis. The reduction of ALT levels, HBV DNA levels, the rate of ALT normalization, undetectable HBV DNA, HBV e antigen (HBeAg) loss, HBeAg seroconversion and mortality were similar between the two groups ( Lian et al., 2013 ; Peng et al., 2014 ). Our data showed that both of the virological response rate and ALT normalization rate were higher after 12-month therapy in ETV monotherapy group compared with combination group.…”
Section: Discussionmentioning
confidence: 94%
“…Por otro lado, a partir de distintas revisiones sistemáticas (35,36) , ETV ha demostrado buena respuesta antiviral en pacientes näive con niveles más avanzados de enfermedad (METAVIR F3-F4), aunque la mortalidad no se afecta significativamente. Aún no se han reportado resultados de efectividad con TDF en enfermedad hepática avanzada.…”
Section: Discussionunclassified